1962
DOI: 10.1149/1.2425206
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Some Addition Agents on the Kinetics of Copper Electrodeposition from a Sulfate Solution

Abstract: The manner in which certain organic addition agents affect the crystal growth of copper electrodeposits was investigated with the aid of the rotating disk electrode technique. The results indicate that thiourea and 1 (−) cystine are cathodically reduced during copper plating. It is proposed that thiourea and 1 (−) cystine, or their reduction products, decompose to form sulfide ions which combine with cupric ions and precipitate as normalCuS on the cathode. Gelatin inhibits pyramidal crystal growth at low cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…Rotating disk electrode kinetics experiments by Rudy (9) established that the Cubath| M and Cubath| 1 additives in use do not cause significant changes in either the copper kinetics or the diffusion coefficient of the copper ions in solution. Similar results were obtained by Turner and Johnson (10,11) for copper sulfate solutions with several different additives; although their work shows that some additives can affect kinetics. These results are consistent with the review papers by which discuss the effects of additives in several plating systems.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Rotating disk electrode kinetics experiments by Rudy (9) established that the Cubath| M and Cubath| 1 additives in use do not cause significant changes in either the copper kinetics or the diffusion coefficient of the copper ions in solution. Similar results were obtained by Turner and Johnson (10,11) for copper sulfate solutions with several different additives; although their work shows that some additives can affect kinetics. These results are consistent with the review papers by which discuss the effects of additives in several plating systems.…”
supporting
confidence: 88%
“…It has also been recommended as a substitute, or as an underplating for gold on copper printed circuit boards (9)(10)(11). Certain fundamental characteristics of the alloy which have technological importance are its corrosion resistance or passivity, and its thermal stability.…”
Section: Discussionmentioning
confidence: 99%
“…These logarithmic spirals were precisely the correct angle, and Tsuda's work rebutted a less accurate measurement of dissolution spiral angles by Johnson and Turner [45]. Those authors had maintained that the spirals were Archimedean, and although the difference is small, the consonance between Tsuda's and Cochran's results shows that dissolution spirals and striae follow the flow lines close to the disk surface.…”
Section: Striated Zinc Electrodepositsmentioning
confidence: 89%
“…8 increasing the rate of reduction (Franklin, 1987). Experiments to investigate the effects of the addition of thiourea, 1(-) cystine, glycine, gelatine, and dextrin on acid copper electroplating showed that addition of glycine and dextrin had no effect on the polarization (i.e., current vs. voltage) curve from those without the additive, whereas the other additives did influence the polarization, but the behavior differed from one another Johnson and Turner, 1962). Kardos and Foulke (1 962) noted that some additives do not appreciably influence the charge transfer kinetics or mass transfer processes in the acid copper system used.…”
Section: Aiche Journalmentioning
confidence: 98%